Inspired by an ancient Chinese Medicine prescription: the modern significance and potential of Yiyi Fuzi Baijiang San in treating diseases - Zhang, Yuli; Zhang, Lu; Chai, Ni; Wan, ZhiQiang; Sui, Hua (Frontiers in Pharmacology, 2024)
Classic Formulas (Jing fang) are considered the essence and authority of Traditional Chinese Medicine (TCM) due to their long history and proven efficacy. These formulas play a pivotal role in all kinds of different disease prevention and therapeutic strategies. Yiyi Fuzi Baijiang San (YYFZBJS), one of the Classic Formulas, was originally developed for the treatment of chronic intestinal abscess. With the accumulation of clinical experience and the exploration of modern pharmacological research in recent years, YYFZBJS has been extensively employed to address a broad spectrum of conditions such as colorectal cancer. Although numerous studies have explored the clinical efficacy and underlying mechanisms of YYFZBJS, no comprehensive review summarizing these findings exists to date. This study aims to systematically review and critically assess the current clinical and mechanistic research on YYFZBJS, with the objective of providing valuable insights and guidance for TCM research in the future.